1999
DOI: 10.1093/humrep/14.6.1642
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotrophin concentrations in early pregnancy after in-vitro fertilization

Abstract: There is increased risk of early pregnancy loss after assisted reproduction. In this study the use of serum human chorionic gonadotrophin (HCG) concentrations on day 12 after in-vitro fertilization (IVF) and embryo transfer was evaluated to predict pregnancy outcome. A total of 417 IVF pregnancies were included. Early pregnancy loss was defined as biochemical pregnancies, ectopic pregnancies and first trimester abortions. Vital pregnancies were defined as delivered singletons, multiple pregnancies and second t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 25 publications
2
53
1
1
Order By: Relevance
“…Several studies have reported various cutoff values of initial serum hCG-β levels, drawn a specific number of days after ET to be useful in distinguishing viable with non-viable pregnancies in the early postimplantation period after ART with reasonable sensitivity and specificity [12,[16][17][18][19][20][21][22][23][24][25]. Additionally, serial serum hCG-β levels and the application of established logarithmic curves were reported to offer more reliable results for assessing pregnancy progression [2,21,25].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported various cutoff values of initial serum hCG-β levels, drawn a specific number of days after ET to be useful in distinguishing viable with non-viable pregnancies in the early postimplantation period after ART with reasonable sensitivity and specificity [12,[16][17][18][19][20][21][22][23][24][25]. Additionally, serial serum hCG-β levels and the application of established logarithmic curves were reported to offer more reliable results for assessing pregnancy progression [2,21,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, while several studies conclude that a single hormone measurement in early pregnancy can reliably predict pregnancy outcome (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), other reports suggest that serial hormone determinations for differential diagnosis of early pregnancy are superior to single measurements with regard to diagnostic power (15)(16)(17)(18). On the other hand, while most of those previous reports relied on the use of HCG as a single marker in early pregnancy (5)(6)(7)(8)(9)(10)12,14,15,17,18), others investigated also the prognostic value of serum progesterone and estradiol as predictors of early gestational normalcy (11,16,19). Therefore, this study was undertaken to investigate the relative power of HCG, estradiol, and progesterone determinations in the prediction of pregnancy outcome after IVF.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of such variation remain largely unknown. The increased hCG concentrations in multiple pregnancies (9) are probably due to the higher number of trophobast cells than in singleton pregnancies. Paracrine and autocrine regulations of hCG synthesis are likely to exist but are poorly understood (4,10).…”
mentioning
confidence: 95%